Mental Health Issue Accelerates Aging Faster than Smoking – Study Rings Alarm for Pakistan where it still remains a Taboo! - Noman Adil; Aruba Jamal; Sumbul Soha (Journal of the Pakistan Medical Association, 2023)
Madam, Mental health is defined as a state of mental well-being that enables people to cope with the stresses of life, realise their potential, learn and work well, and contribute to their community as a whole. (1) A recently published study in the journal Aging (2), revealed that mental health can be more deteriorating than smoking. The researchers used an ageing clock to measure how it impacted the pace of aging in 12,000 Chinese adults. Researchers found that smoking speeds up the rate of ageing by 1.25 years whereas mental health factors accelerated it by 1.65 years. The aging clock used blood, DNA and genetic test of individuals to measure their biological aging pace. The mental health variables tested included Depression, Sleep Issues, Hopelessness, Feeling unhappy, Loneliness, Married, Widowed, and Living in a Rural area. (2) Ageing directly predisposes individuals to diseases like Diabetes Type 2, Cancer, Cardiovascular and Neurological disorders which significantly affect the lifestyle and lifespan of individuals.(3) Talking about mental health is still seen as Taboo in Pakistan, and that’s why people don’t consider consulting about their mental health issues. Statistics have revealed that more than 14 million Pakistanis suffer from some sort of psychiatric illness and the majority of these believe that these are caused by supernatural forces such as spirit possession etc. This is mainly due to lack of awareness about mental disorders and shortage of mental health professionals. (4) The modern study showing mental health factors accelerated ageing faster than smoking (2), is an eye-opener and alarm for our society where we now do stress upon the hazardous effects of smoking, we also need to equally emphasize about working on Mental Health awareness on mass scales utilising media, health policies, and community health care programmes. Family is the primary source of your nurturing, and it is necessary to make Parents also realise that they should establish such a relation with their children that they can easily talk about any of their issues comfortably with them. An emphasis on considering mental health issues need serious professional consultation. Along with keeping a balanced life, spending quality time with family and friends, ease of interaction is needed to ensure that our population doesn’t fall prey to these issues and cost them their whole life.